EVALUASI MANFAAT DAN BIAYA PENGURANGAN EMISI SERTA PENYERAPAN KARBON DIOKSIDA PADA LAHAN GAMBUT DI HTI PT. SBA WI - Rahmat, Mamat (Bumi Lestari; Vol 10 No 2 (2010), 2010)
Forest has an opponent function in climate change issue, as carbon sink and carbon source. Reducing emission from deforestation and forest degradation (REDD) is the mechanism to tackle green house gas emission from forest sector. The economic analysis of those projects in Indonesia has not conducted yet, moreover the benefit and cost analysis of REDD on forest management unit. The research was conducted in the unique site, at Industrial Forest Plantation PT. SBA WI, South Sumatera. Benefit and cost analysis and break-even cost analysis were conducted to evaluate project feasibility. The research result shows that forest management was not feasible if the role of the project aimed to product wood or reducing emission only which conducted in mutual. If the project aims to reach both roles together, it is very attractive. Break-even cost of reducing emission and carbon sequestration in PT. SBA WI Rp.29.000,- per ton CO2e equal to US$3,17. It was lower than the cost in Bolivia, Ghana, and Nepal and also cheaper than carbon price in voluntary market.
Keywords: benefit and cost analysis; carbon sequestration; emission reduction; forest plantation; peat land